Change in Strain-Strength Indices of Extracellular Matrix After Its Decellularization - Popandopulo, Andrey G.; Savchuk, Marina V.; Yuditsky, Dmitriy L. (Problems of Cryobiology and Cryomedicine, 2014)
Tissue-engineered grafts of valves are current solution of prostheses medical problem and able of proper substituting the mechanical valvular prostheses. These prostheses are based on using decellularized connective tissue matrix. The research was aimed to design extracellular matrix close to native on morphological and physical properties after decellularization to create valvular-vascular biological graft. The research results demonstrated that the tissue strain and strength were preserved and therefore the matrix could be used as a scaffold for prostheses. Probl Cryobiol Cryomed 2014; 24(4):346-353.